Bantuan Kemanusiaan UNICEF terhadap Anak-Anak terdampak Kelaparan dan Malnutrisi dalam Konflik Yaman - Nugraha, Farhan Arda; Deasy Silvya Sari; Kiagus Zainal Mubarak (Indonesian Journal of Global Discourse, 2024)
Since 2014, the ongoing civil war in Yemen has resulted in a food crisis. About 20 million Yemenis are starving and 2 million of them are children. This article aims to lay out the situation of children's food security in Yemen and UNICEF's humanitarian assistance program in addressing the hunger and malnutrition experienced by Yemeni children due to the Yemen conflict. The concepts used to analyze are conflict, food security, and humanitarian assistance. The method used is qualitative with data collection techniques in the form of archival and document-based research and internet-based research. This article found that UNICEF has undertaken humanitarian assistance programs to address the hunger and malnutrition crisis caused by the civil war in Yemen. UNICEF works closely with local parties such as the Yemeni government and various international humanitarian organizations. UNICEF humanitarian assistance, includes: providing food supplies, medicines, vitamins and the construction of health centers.